Looking for Mickey Mouse™ But Finding a Munchkin: The Perceptual Effects of Frequency Upshifts for Single-Sided Deaf, Cochlear Implant Patients - Dorman, Michael F. (J Speech Lang Hear Res, 2019)
PURPOSE: Our aim was to make audible for normal-hearing listeners the Mickey Mouse™ sound quality of cochlear implants (CIs) often found following device activation. METHOD: The listeners were 3 single-sided deaf patients fit with a CI and who had 6 months or less of CI experience. Computed tomography imaging established the location of each electrode contact in the cochlea and allowed an estimate of the place frequency of the tissue nearest each electrode. For the most apical electrodes, this estimate ranged from 650 to 780 Hz. To determine CI sound quality, a clean signal (a sentence) was presented to the CI ear via a direct connect cable and candidate, and CI-like signals were presented to the ear with normal hearing via an insert receiver. The listeners rated the similarity of the candidate signals to the sound of the CI on a 1- to 10-point scale, with 10 being a complete match. RESULTS: To make the match to CI sound quality, all 3 patients need an upshift in formant frequencies (300–800 Hz) and a metallic sound quality. Two of the 3 patients also needed an upshift in voice pitch (10–80 Hz) and a muffling of sound quality. Similarity scores ranged from 8 to 9.7. CONCLUSION: The formant frequency upshifts, fundamental frequency upshifts, and metallic sound quality experienced by the listeners can be linked to the relatively basal locations of the electrode contacts and short duration experience with their devices. The perceptual consequence was not the voice quality of Mickey Mouse™ but rather that of Munchkins in The Wizard of Oz for whom both formant frequencies and voice pitch were upshifted. SUPPLEMENTAL MATERIAL: https://doi.org/10.23641/asha.9341651